Peningkatan Kesadaran Budaya Berbasis Health IT Psiko Melalui Program Literasi Tech-Psy di lingkungan Pendidikan - Hidayat, Wahyu; Wulandari, Yuni; Hasanah, Uswatun; Surbakti, Seni Sehati (Unity Academy, 2025)
The digital transformation in education requires enhanced cultural awareness that adapts to technological advancements and mental health dynamics. This study aims to develop and implement the Tech-Psy literacy program as a strategy to improve cultural awareness based on Health IT Psycho within educational settings. The approach integrates health information technology (Health IT) with educational psychology principles to foster healthy, empathetic, and culturally grounded digital behavior. The methods employed include surveys, digital-psychological literacy training, and qualitative evaluation of changes in participants’ attitudes and awareness. The results indicate that the implementation of the Tech-Psy program significantly increases participants’ understanding of digital ethics, mental health awareness in technology use, and appreciation of local cultural values within the context of digital globalization. Moreover, a positive correlation was found between Tech-Psy literacy levels and socio-emotional adaptability in digital spaces. These findings suggest that integrating Health IT Psycho into education not only supports mental well-being but also strengthens cultural identity in the technology era. The program is recommended as a model for developing psychosocial and culture-based digital literacy in Indonesian educational institutions.